Rural Schooling in Mobile Modernity: Returning to the Places I've Been - Michael Corbett (Journal of Research in Rural Education, 2009)
In my book Learning to Leave: The Irony of Schooling in a Coastal Community (Corbett, 2007) I make the claim that there is a deep and established connection between formal education and mobility out of rural areas. The book reports on a study undertaken in a coastal community in Atlantic Canada focusing on the educational and life experiences of those who persisted and those who left the community during the economic and social changes from the late 1950s to the late 1990s. The book argues that place matters in a multitude of ways despite persistent attempts to erase and neutralize its influence in educational thought, policy, pedagogical practice and curriculum. Because I want to resist the abstract academic conventions also resisted by my informants, and because I want to argue that place should occupy a more central place in the way we think about and deliver education, this article situates my own analysis of what I think the book means in the actual places that grounded its conception.